DARI KELAS KE REALITAS: MENGAPLIKASIKAN NILAI-NILAI PANCASILA DALAM KEHIDUPAN SEHARI HARI - Hendra Rahayu; Yakobus Ndona; Daulat Saragi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the application of Pancasila values ​​in students' activities at school, at home, and in the community. Using a descriptive qualitative approach, data were collected through observations, interviews, and documentation with the principal, teachers, and students at SDN 101738 Diski. The results indicate that the internalization of Pancasila values ​​is reflected in students' daily habits, including religious attitudes, discipline, cooperation, tolerance, and responsibility. The application of these values ​​is reinforced by familiarization at school and support from family and the community. This study confirms that Pancasila-based character education plays a crucial role in shaping moral, critical, and competitive individuals as the nation's next generation.